2015
DOI: 10.1016/j.cortex.2015.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the neural network of facial mimicry of smiles – An rTMS study

Abstract: a b s t r a c tUnder theories of embodied emotion, exposure to a facial expression triggers facial mimicry. Facial feedback is then used to recognize and judge the perceived expression.However, the neural bases of facial mimicry and of the use of facial feedback remain poorly understood. Furthermore, gender differences in facial mimicry and emotion recognition suggest that different neural substrates might accompany the production of facial mimicry, and the processing of facial feedback, in men and women. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 68 publications
2
61
0
1
Order By: Relevance
“…Importantly, Niedenthal and colleagues' three studies (2012) consistently showed that the associations of pacifier use with decreases in these skills were found only in boys and young men. The authors interpret these gender differences in light of the existing literature on sex differences in emotional socialization: the development of emotion competences is generally slower and more fragile in men than in women (Zahn-Waxler et al, 1992;Brody, 2000;Korb et al, 2015). In addition, evidence shows that females tend to recognize emotion expressions more accurately than males (e.g.…”
Section: Pacifiers and Emotional Competence Of Young Adultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Importantly, Niedenthal and colleagues' three studies (2012) consistently showed that the associations of pacifier use with decreases in these skills were found only in boys and young men. The authors interpret these gender differences in light of the existing literature on sex differences in emotional socialization: the development of emotion competences is generally slower and more fragile in men than in women (Zahn-Waxler et al, 1992;Brody, 2000;Korb et al, 2015). In addition, evidence shows that females tend to recognize emotion expressions more accurately than males (e.g.…”
Section: Pacifiers and Emotional Competence Of Young Adultsmentioning
confidence: 81%
“…In addition, facial mimicry is only a part of sensorimotor processes (Wood et al, 2016), and the ability to simulate a movement may be more important than performing it. Such interpretation is supported by evidence that inhibiting the activity of primary motor brain regions, which are involved in generating facial mimicry, disrupts the recognition of smiles to a greater extent than inhibiting the activity of somatosensory brain areas, which are arguably involved in receiving feedback from the face (Korb et al, 2015). Altogether, sensorimotor simulation is a complex and poorly understood phenomenon that needs further exploration given its importance in social learning (e.g.…”
Section: Embodied Simulation and Emotion Recognitionmentioning
confidence: 98%
“…On the other hand, excitatory high-frequency rTMS of the MPFC enhances mimicry of facial expressions in CS and ZM muscles during an empathic, emotional task (Balconi and Canavesio, 2013). Recently, Korb et al (2015) have found that inhibition (rTMS) of both right primary motor cortex (M1) and the right primary somatosensory cortex (S1), considered as a part of MNS (for review see Pineda, 2008), also led to reduced facial mimicry. Together, these data suggest that the increased mimicry of facial expressions in highly empathic individuals is mediated by greater activation of empathy-related neural networks.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of the literature on mimicry elucidates its relationship with emotional contagion, widely believed to be a component of emotional empathy [Chartrand & Lakin, ]. The extent to which SFM is modulated by top–down processes [Hamilton, ] and/or by one's own emotional state [Hess & Fischer, ], as well as its neural correlates [Korb et al, ], constitutes an area of active research. Direct eye contact between the sender and the receiver of an emotional facial expression has been suggested to be a trigger for SFM [Niedenthal, Mermillod, Maringer, & Hess, ], and modulates the mimicry of hand movements [Wang, Newport, & Hamilton, ].…”
Section: Introductionmentioning
confidence: 99%